Aportes a la colección de hongos liquenizados del herbario del Instituto de Botánica Carlos Spegazzini (LPS) - Lavornia, Juan Manuel (2017)
Contributions to the collection of liquenized fungi from the herbarium of the Institute of Botany Carlos Spegazzini (LPS). The Institute of Botany Carlos Spegazzini (IBCS) (UNLP, La Plata) hosts an herbarium of fungi (LPS) of approximately 40,000 specimens, with 4200 type specimens. The aim of this study was to examine the specimens of lichenized fungi deposited in the IBCS, update their taxonomy and name, check questionable species determination, identify those not certain, and incorporate them into the Herbarium LPS. 192 specimens were studied coming from 11 Provinces of Argentina, as well as Brazil, Uruguay and France and they were determined based on their exo-morphology, histological and histochemical reactions. Thin Layer Chromatographs (TLC) were also performed to study the secondary metabolites present. Argentinean geographical distribution of the identified species was established. The 91.66% of the materials examined (176 specimens) was corrected and accounted for a total of 91 species, 50 genera and 21 families, with Parmeliaceae (16 genera, 31 species), Graphidaceae (4; 5) and Physciaceae (3; 9) as the best represented. The name of 56 specimens belonging to 32 species was updated. The identity of 120 specimens was modified to species level (87), genera (33) and family (1). The distribution of 9 species in Argentina was expanded.